2019
DOI: 10.5713/ajas.17.0138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental enrichment on behaviour, physiology and performance of pigs — A review

Abstract: The aim of this paper is to critically analyse and synthesise existing knowledge concerning the use of environmental enrichment and its effect on behaviour, physiology and performance of pigs housed in intensive production systems. The objective is also to provide clarity as to what constitute successful enrichment and recommend on when and how enrichment should be used. Environmental enrichment is usually understood as an attempt to improve animal welfare and to lesser extent, performance. Common enrichment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 69 publications
(131 reference statements)
0
54
0
Order By: Relevance
“…Enrichment reduced aggression before, but not after weaning. Beattie and O'connell (17) found a reduction in aggression in pigs provided with extra space and rooting substrates, whereas studies comparing similar sized pens with or without rooting substrates reported either no effect (11,51), a decrease (57) or an increase in aggression (58,59). Thus, effects of enrichment on aggression seem inconsistent.…”
Section: Effects Of Enrichment Before the Switchmentioning
confidence: 99%
“…Enrichment reduced aggression before, but not after weaning. Beattie and O'connell (17) found a reduction in aggression in pigs provided with extra space and rooting substrates, whereas studies comparing similar sized pens with or without rooting substrates reported either no effect (11,51), a decrease (57) or an increase in aggression (58,59). Thus, effects of enrichment on aggression seem inconsistent.…”
Section: Effects Of Enrichment Before the Switchmentioning
confidence: 99%
“…Pastures are complex ecosystems where a great variety of elements and organisms interact. They are similar to the environments in which pigs evolved, and consequently better suited to fulfil their physiological and psychological needs than other systems [24,27]. Pasture and indoor-confinement rearing environments differ considerably and might generate differences in the welfare of pigs managed in those production systems.…”
Section: The Pasture Environmentmentioning
confidence: 94%
“…Compared with other systems, pasture systems offer pigs a greater opportunity to carry out more physical activity [6], which would result in better animal welfare [35,108]. The impossibility of behaving naturally due to confinement, and the privation of environmental stimulation have been identified among the main causes of boredom and frustration in indoor managed pigs [24,39]. Additional potential consequences to lack of exercise are more health related: impairment of the cardiovascular system, and weakness of bones and muscles which frequently cause lameness [41].…”
Section: Exercisementioning
confidence: 99%
“…Provision of enrichment can prevent or reduce tail-directed behaviours [ 4 , 5 ], improve pigs’ emotional state [ 6 ] and improve pig performance [ 7 ]. In general, loose organic material, such as straw (from a handful to deep straw-bedding), is considered to be the gold standard.…”
Section: Introductionmentioning
confidence: 99%